Syntactic awareness and reading comprehension: a systematic review of cross-linguistic transfer - Xinzi Ouyang; Nurjanah Mohd Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2025)
Syntactic awareness or the ability to reflect on and manipulate grammatical structures is a key component of reading comprehension. While individual studies show that syntactic awareness may support cross-language reading comprehension, prior literature reviews have not examined syntactic awareness as a distinct construct, leaving unclear how syntactic transfer varies across language pairs, learner profiles, and instructional contexts. A systematic literature review is therefore needed to clarify the extent and nature of this transfer in varied contexts. This article presents a systematic literature review synthesizing empirical evidence from 2015 to 2025 on how syntactic awareness transfers across languages to influence reading comprehension. Guided by PRISMA protocols, a total of 953 studies were selected from three databases, namely, ProQuest, Web of Science, and ERIC, and only 23 peer-reviewed studies were systematically reviewed regarding their research designs, participant demographics, language pairings, and methodological limitations. This review finds that current research is largely cross-sectional, using regression or structural equation modeling (SEM) with varied syntactic awareness and reading measures, and is dominated by studies on primary immersion learners and a narrow set of language pairings. Although previous research has produced mixed findings, this review finds overall support for the positive role of syntactic awareness transfer in reading comprehension across languages. However, this relationship is influenced by factors such as vocabulary and word reading. The review recommends the adoption of more longitudinal, experimental, and mixed-methods research designs, along with greater inclusion of adult participants and linguistically diverse populations. It also emphasizes the need to validate bilingual syntactic awareness instruments in order to deepen the understanding of syntactic awareness transfer in reading comprehension.